Pelatihan Scientific Writing Berbasis Situasi Problematik sebagai Upaya Peningkatan Prestasi dan Literasi - Hidayatullah, Hengki Tri; Izza, Jasmine Nurul; Ardyansyah, Ananta; Setiyowati, Arbin Janu (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: We developed a guidebook for writing scientific papers to improve the achievement and literacy of MAN 1 Mojokerto students. The purpose of this community service is to increase students’ knowledge and references to improve their writing skills. Methodology/approach: The service was conducted through the asset-based community development (ABCD) method followed by 5D steps. Results: The training participants were MAN 1 Mojokerto students. MAN 1: Mojokerto students initially had no knowledge of writing. They had difficulty in writing scientific papers. MAN 1: Mojoketo students had difficulty understanding the structure of scientific papers, good scientific criteria, and how to develop scientific ideas. After training using the scientific writing guide, the students felt more confident in writing scientific papers. Students did not experience these difficulties. Limitations: The scientific writing guidebook contains procedures for writing scientific papers and specifically discusses several models of scientific papers, namely, popular scientific articles, scientific essays, and scientific papers in competitions. Contribution: The guidebook for writing scientific papers is considered by students to be easy to understand and helpful in improving their skills and understanding related to scientific papers. At the end of the program, students were able to write scientific papers. Therefore, the scientific writing book can improve students' understanding of scientific work, thereby increasing their achievement and literacy.